2016
DOI: 10.1021/acs.langmuir.6b01674
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interactions between Air Bubble and Hydrophobic Polymer Surface: Impact of Solution Salinity and Interfacial Nanobubbles

Abstract: The interactions between air bubbles and hydrophobic polymer surfaces in aqueous media play important roles in many industrial and engineering processes. In this work, the interaction forces between air bubble and a model hydrophobic polymer-polystyrene (PS) in NaCl solutions (1 mM to 1000 mM) were directly measured using a bubble probe atomic force microscope (AFM) technique, and the measured forces were analyzed by a theoretical model based on Reynolds lubrication theory and augmented Young-Laplace equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 60 publications
2
45
1
Order By: Relevance
“…Now, the only unknown parameter for hydrophobic potential calculation is the decay length. Recent studies have shown that D is system-dependent [8,34,35]. Donaldson et al [36] reviewed the current hydrophobic force experimental results and found that a decay length of 0.3-2 nm in a general exponential decay law is able to describe all the intrinsic hydrophobic forces.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Now, the only unknown parameter for hydrophobic potential calculation is the decay length. Recent studies have shown that D is system-dependent [8,34,35]. Donaldson et al [36] reviewed the current hydrophobic force experimental results and found that a decay length of 0.3-2 nm in a general exponential decay law is able to describe all the intrinsic hydrophobic forces.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The HB interaction between air bubble and OTS‐mica substrate was reported to follow an exponential relation, as described in Equation , where D 0 is the decay length of HB interaction, γ AW is the air/water interfacial tension, and θ c is static the water contact angle on the OTS–mica substrate , trueHB[]h()r,t=-C0D0prefixexp()-h()r,tD0=-γAW()1-prefixcosθcD0prefixexp()-h()r,tD0 …”
Section: Methodsmentioning
confidence: 99%
“…P Laplace can be obtained by solving the Young–Laplace Equation (Equation ) PLaplace = 2γR γrr rhrwhere, R is the radius of the bubble and γ is the surface tension of the liquid. The disjoining pressure (surface force per unit area) originates from different surface force components namely Vanderwaals (VdW), electrostatic double layer (EDL) as well as hydrophobic interactions (HB) (Equations –) . For a given solid–liquid–vapor system, Vanderwaals component normalVdW[h(r,t)] = AnormalH(6πh3 (r,t)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The interaction between disjoining pressure (surface force per unit area) and Laplace pressure of the bubble determines its adhesive or repulsive behavior in a liquid medium. If the negative disjoining pressure (attractive) overcomes the Laplace pressure, thin liquid film gets destabilized and bubble attachment occurs . The stability of liquid film contributed by the repulsive Vanderwaals force offers little possibility for bubble adhesion.…”
Section: Theoretical Backgroundmentioning
confidence: 99%